2017
DOI: 10.1101/186148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APC/CFZR-1Controls SAS-5 Levels to Regulate Centrosome Duplication inCaenorhabditis elegans

Abstract: As the primary microtubule-organizing center, centrosomes play a key role in establishing mitotic bipolar spindles that secure correct transmission of genomic content. For the fidelity of cell division, centrosome number must be strictly controlled by duplicating only once per cell cycle. Proper levels of centrosome proteins are shown to be critical for normal centrosome number and function. Overexpressing core centrosome factors leads to extra centrosomes, while depleting these factors results in centrosome d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…Thus, loss of FZR-1 leads to increased levels of ZYG-1 at centrosomes, which should compensate for impaired ZYG-1 function and rescue the zyg-1 mutant phenotypes observed previously (Kemp et al, 2007, Medley et al, 2017a. These results support a hypothesis that ZYG-1 levels are regulated by APC/C FZR-1 -dependent proteasomal degradation.…”
Section: Loss Of Fzr-1 Leads To Elevated Zyg-1 Levels At Centrosomessupporting
confidence: 75%
See 4 more Smart Citations
“…Thus, loss of FZR-1 leads to increased levels of ZYG-1 at centrosomes, which should compensate for impaired ZYG-1 function and rescue the zyg-1 mutant phenotypes observed previously (Kemp et al, 2007, Medley et al, 2017a. These results support a hypothesis that ZYG-1 levels are regulated by APC/C FZR-1 -dependent proteasomal degradation.…”
Section: Loss Of Fzr-1 Leads To Elevated Zyg-1 Levels At Centrosomessupporting
confidence: 75%
“…Prior study identified SAS-5 as a substrate of APC/C FZR-1 , and implicated that APC/C FZR-1 might target additional centrosome regulators in C. elegans embryos (Medley et al, 2017a). The APC/C coactivator, FZR-1, was identified as a genetic suppressor of ZYG-1 since loss of fzr-1 restores embryonic viability and centrosome duplication to the zyg-1(it25) mutant (Kemp et al, 2007;Medley et al, 2017a). Given the strong genetic interaction between zyg-1 and fzr-1, a compelling possibility is that ZYG-1 might be a substrate of APC/C FZR-1 .…”
Section: Loss Of Fzr-1 Leads To Elevated Zyg-1 Levels At Centrosomesmentioning
confidence: 99%
See 3 more Smart Citations